Pengaruh Hidroterapi (Rendam Kaki Air Hangat) Terhadap Tekanan Darah Pada Pasien Hipertensi - Librianty, Rina (Jurnal Kesehatan Bhakti Husada, 2024)
Hypertension, if not treated immediately, can cause various complications. One non-pharmacological therapy that can lower blood pressure is hydrotherapy (soaking the feet in warm water). Hydrotherapy (warm water foot soak) is a water therapy that can lower blood pressure. Hydrotherapy (soaking your feet in warm water) can dilate blood vessels, thereby improving blood circulation and lowering blood pressure. The instruments used in this research were a digital Omron Sphygmomanometer and a partial LIG Thermometer that had been calibrated. The population in this study was hypertensive patients in the Berbah Yogyakarta Community Health Center working area with a total of 60 respondents, 30 respondents in the intervention group and 30 respondents in the control group. Data analysis used independent T-test. The average systolic blood pressure in the pretest intervention group was 161.87mmHg, posttest 140.83mmHg. characteristics of respondents in the intervention group with an average age of 67.53 years, junior high school education or lower (70.0%), most of the respondents did not work (73.3%), almost all of the respondents did not smoke (86 .7%), low drug compliance (50.0%). There was an effect of hydrotherapy (soaking the feet in warm water) on blood pressure in the intervention group when the results were obtained (p=0.001). The suggestion in this study is to measure external variables after being given intervention in the intervention group and control group. Please minimize the use of abbreviations and don't cite references in the abstract